2020
DOI: 10.3390/toxins12070432
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacteriocins from Lactobacillus taiwanensis for Producing Bacterial Ghosts as a Next Generation Vaccine

Abstract: Bacteriocins are functionally diverse toxins produced by most microbes and are potent antimicrobial peptides (AMPs) for bacterial ghosts as next generation vaccines. Here, we first report that the AMPs secreted from Lactobacillus taiwanensis effectively form ghosts of pathogenic bacteria and are identified as diverse bacteriocins, including novel ones. In detail, a cell-free supernatant from L. taiwanensis exhibited antimicrobial activities against pathogenic bacteria and was observed to effectively ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Some cells were abnormally longer due to cell elongation or filamentation, the cell membrane changed shape, and intracellular vacuoles were noted ( Figure 4(d) ). A recent study indicated that cell-free supernatant containing peptides produced by Lactobacillus taiwanensis induced ghost cells in Salmonella gallinarum [ 22 ]. Similarly, vacuole formation increases when the cells are treated with antimicrobials [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some cells were abnormally longer due to cell elongation or filamentation, the cell membrane changed shape, and intracellular vacuoles were noted ( Figure 4(d) ). A recent study indicated that cell-free supernatant containing peptides produced by Lactobacillus taiwanensis induced ghost cells in Salmonella gallinarum [ 22 ]. Similarly, vacuole formation increases when the cells are treated with antimicrobials [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently it is reported that L . taiwanensis produce bacteriocins, an antimicrobial peptide [ 45 ]. In the present study, increase in concentration of bacteriocins produced by excessive amount of L .…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of antimicrobial activity on a microtiter plate was performed by some modification of the dilution assay of Wiegand et al [ 27 ]. The MIC50 and MIC90 were expressed as total proteins equivalent (μg) per volume (mL) of the sample, and the effect of proteinase K treatment was examined by a previously described procedure [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The S. Enteritidis was treated with the cell-free supernatant (70.8 μg total proteins/mL, MIC against S. Enteritidis) from L. plantarum culture or the synthetic peptides, Pln 3 (1 μg/μL) or Pln 5 (1 μg/μL), for 0, 1, and 8 h, and the lentivirus was assessed with the cell-free supernatant (15.8 μg total proteins/mL) for 5 min and with the synthetic peptides Pln 3 (5 μg/μL) or Pln 5 (5 μg/μL) for 24 h. The treated bacteria and viruses were observed by a scanning electron microscope according to previously described procedures [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation